Modern nmr techniques for chemistry research - Derome, Andrew E. (New York Pergamon Pr, 1987)
Presents an introduction to modern NMR methods at a level suited to organic and inorganic chemists engaged in the solution of structural and mechanistic problems. The book assumes familiarity only with the simple use of proton and carbon spectra as sources of structural information and describes the advantages of pulse and Fourier transform spectroscopy which form the basis of all modern NMR experiments. Discussion of key experiments is illustrated by numerous examples of the solutions to real problems. The emphasis throughout is on the practical side of NMR and the book will be of great use to chemists engaged in both academic and industrial research who wish to realise the full possibilities of the new wave NMR.
Keywords: chemistry; reasearch